TINJAUAN SISTEMATIS TENTANG TEKNIK DELPHI DAN KAITANNYA TERHADAP ISU KEFARMASIAN TERKINI - Anshar Saud (Faculty of Pharmacy, Hasanuddin University, 2019)
Delphi technique has been knowned in variety research of studies and countries for almost eight decades as one of reliable decision making method. Its success and relation in pharmacy field has been examined but not yet catalogue recently in a comprehensive manner. The objective of this study was to review existing literature studies on the topic of Delphi technique and its relation on current pharmaceutical issues to provide an analysis of its success and impact in pharmacy and health sector. A search of 6 electronic databases i.e: Google Scholar, MEDLINE, PubMed, ScienceDirect, Web of Science and Proquest was conducted during November 2018. A scientific review of literature (2008-2018) was performed to identify and collate information from relevant, peer reviewed original study articles investigating Delphi technique employed in pharmaceutical issues. A thematic analysis was undertaken to categorize categories of pharmacy, pharmaceutical, pharmaceutical care and pharmacist. Thirty two original study articles were included in this review. All articles were based in the U.S., Europe, Australia and Asia. After reviewing all the articles, 5 themes with 13 categories were generated. These themes included essential role of pharmacist in healthcare, pharmacy professionalism, medication management protocol, pharmacy education, and drug policy. It concluded that overall, through this review it is evident that there are a number of themes on pharmacy issues that employed by Delphi techniques. This review indicated that although Delphi technique are successful and to be satisfactory applied in pharmacy field, the usage of technique in pharmacy issues need to be further enhanced.